2015
DOI: 10.1038/nature14684
|View full text |Cite
|
Sign up to set email alerts
|

Cell mixing induced by myc is required for competitive tissue invasion and destruction

Abstract: Cell-cell intercalation is used in several developmental processes to shape the normal body plan. There is no clear evidence that intercalation is involved in pathologies. Here we use the proto-oncogene myc to study a process analogous to early phase of tumour expansion: myc-induced cell competition. Cell competition is a conserved mechanism driving the elimination of slow-proliferating cells (so-called 'losers') by faster-proliferating neighbours (so-called 'winners') through apoptosis and is important in pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
164
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 53 publications
14
164
0
Order By: Relevance
“…Our experimental results and previous findings show that Myc overexpression leads to clone rounding and a reduction of cell-cell contacts with neighboring wt cells (Prober and Edgar, 2002). Although we did not study Mycmediated cell competition and our experimental setup was different from that of Levayer et al (2015), it would be relevant to analyze whether Myc-mediated cell competition also depends on additional mechanisms associated with reduced cell-cell contact formation owing to a decrease of MyoII level. Lastly, our findings on Yki suggest the existence of a possible negative feedback between Yki activation and cell junction tension.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our experimental results and previous findings show that Myc overexpression leads to clone rounding and a reduction of cell-cell contacts with neighboring wt cells (Prober and Edgar, 2002). Although we did not study Mycmediated cell competition and our experimental setup was different from that of Levayer et al (2015), it would be relevant to analyze whether Myc-mediated cell competition also depends on additional mechanisms associated with reduced cell-cell contact formation owing to a decrease of MyoII level. Lastly, our findings on Yki suggest the existence of a possible negative feedback between Yki activation and cell junction tension.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings on the mechanisms of clone rounding provide information on cell competition and on a possible negative feedback between proliferation and tension regulation. In the context of cell competition, it has been recently reported that a clonal decrease of Myc levels, or a clonal increase of Myc levels in conjunction with an inhibition of apoptosis, promotes clone fragmentation and cell mixing; such cell-cell mixing increases cell-cell contacts and depends on reduced levels of F-actin, independently of changes in MyoII levels (Levayer et al, 2015). Our experimental results and previous findings show that Myc overexpression leads to clone rounding and a reduction of cell-cell contacts with neighboring wt cells (Prober and Edgar, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, expression of the loseA and loseB isoforms of fwe in a subset of cells is sufficient to induce their elimination in the Drosophila wing imaginal disc epithelia [28], while only the loseB isoform can induce loser status in neurons [33,39,42]. It has been recently shown that loser elimination correlates with the relative concentrations of fwe loseA or loseB isoforms in winner and loser cells, as well as the surface contact shared between winner and loser cells [45]. This finding suggests that each cell can compute and compare fwe loseA or loseB levels with all its neighbors.…”
Section: Elimination Through Fitness Fingerprintsmentioning
confidence: 97%
“…In this situation, fitness comparison would require direct contact between winner and loser cells. Accordingly, several studies of the pattern of loser cell elimination have suggested that the recognition and killing process acts at a short range [16,17,19,36,44] or is strictly contactdependent [28,45,46].…”
Section: Elimination Through Fitness Fingerprintsmentioning
confidence: 99%
“…Here we focus on the last steps of this cell selection process, when 'unfit cells' that did not obtain enough survival factors are excluded from the tissue and engulfed by other cells [9][10][11][12] . In particular, we address the question whether the chemotactic signals originated from the dying cells direct their own engulfment.…”
mentioning
confidence: 99%